The entry and super-entry in a dictionary of idioms - Tafra Branka Z. (Južnoslovenski Filolog, 2021)
This discussion of the entry and super-entry is the one that concerns both the internal and external boundaries of the idiom and the identity of the idiom and its components. It gives rise to three groups of issues. The first group includes the theoretical solutions that have already been implemented in Croatian idiomatic lexicography, which constitute a significant shift in comparison to the previous state of linguistic knowledge. The greatest shift undoubtedly lies in the demarcation between polysemy and conversion and in the introduction of a multiword expression as a super-entry. The second group involves proposing the strategies that can be applied in idiomatic dictionaries, such as drawing a clearer distinction between idiom variation and synonymy and identifying the occurrences of onymization and deonymization of components. The third group of issues uncover the dilemmas that seek solutions. First and foremost, what needs to be resolved is the question of the nature of semi-compound words. If they are to be treated as lexemes, which some of them are, then they cannot be categorized as idioms, and if they are to be treated as phrases that can turn into idioms, then they cannot be categorized as semi-compound words, since the latter represents a term from the area of word-formation.